Changes in friction, surface roughness, and tensile strength upon compaction of Ficus deltoidea powder - Ooi, T. C.; Yusof, Yus Aniza; Chin, Nyuk Ling; A. Talib, Rosnita; Othman, Siti Hajar; Aziz, M. G. (Science Society of Thailand, 2013)
The study is concerned with the quantitative measurement of changes in friction, surface roughness, and tensile strength during the compaction of Ficus deltoidea powder, a well-known Malaysian herb. In the compaction process, the force applied for compaction (upper punch) was greatly influenced by the friction between die wall and powder bed during transmission to the lower punch. Wall friction was found to increase with the increasing load and weight of powder due to an increase in surface contact with the die wall. The coefficients of wall friction decreased from 0.47 to 0.36 for increasing weight of powder from 0.8–1.5 g. Tablets with a higher compaction load of 9.5 kN had a lower arithmetic mean deviation (Ra), an indicator of surface roughness. Ra for the top surface is lower than that of for the bottom surface.